From means to margins: The uneven effects of hiring market concentration on the gender wage gap in Germany - Mariya Afonina; Katrin Rickmeier (Bielefeld University, Faculty of Business Administration and Economics, 2025)
In this paper, we study the impact of monopsony power on the gender wage differentials at various parts of the wage distribution from 2019 to 2022. We are measuring hiring labour market concentration by constructing the HHI on the basis of online job advertisement data from Germany.The wages and a rich set of demographic characteristics are acquired from the German Socio-Economic Panel. With the help of RIF-IV, we establish that the impact of labour market concentration is more pronounced in higher deciles of the distribution for the aggregated sample, reaching -2.4% for the monthly wages and -9.6% for the hourly ones. Respective values for the medians equal to -0.9% and -4.7%. However, disaggregating by sex reveals different distributional effects for women and men. For men, the effects are consistent with the aggregated sample, where the impact is insignificant in the lower deciles and increases towards the upper end. For women, however, the impact is highest at the lower and upper deciles and the set of effects demonstrates a hump-shape. Furthermore, women in western Germany are considerably more affected than women in the East. The findings suggests that hiring labour market concentration contributes to a widening of the gender wage gap especially at the lower end of the wage distribution.
urn:nbn:de:0070-pub-30060261
Keywords: J31; J42; R10; R23; 330; labour market concentration; gender inequality; RIF; IV